Introduction to computational biology maps, sequences, and genomes : interdisciplinary statistics - Waterman, Michael S. (Boca Raton, Fla. Chapman & Hall/CRC, 1995)
Biology is at the beginning of a new era, promising significant discoveries that will be characterized by information-packed databases. This text offers a textbook treatment of the combinatorial and statistical problems that will arise in this new era
PrefaceIntroduction Molecular Biology Mathematics, Statistics, and Computer ScienceSome Molecular Biology DNA and Proteins The Central Dogma The Genetic Code Transfer RNA and Protein Sequences Genes Are Not Simple Biological ChemistryRestriction Maps Introduction Graphs Interval Graphs Measuring Fragment SizesMultiple Maps Double Digest Problem Classifying Multiple SolutionsAlgorithms for DDP Algorithms and Complexity DDP is N P-Complete Approaches to DDP Simulated Annealing: TSP and DDP Mapping with Real DataCloning and Clone Libraries A Finite Number of Random Clones Libraries by Complete Digestion Libraries by Partial Digestion Genomes per MicrogramPhysical Genome Maps: Oceans, Islands, and Anchors Mapping by Fingerprinting Mapping by Anchoring An Overview of Clone Overlap Putting It TogetherSequence Assembly Shotgun Sequencing Sequencing by Hybridization Shotgun Sequencing RevisitedDatabases and Rapid Sequence Analysis DNA and Protein Sequence Databases A Tree Representation of a Sequence Hashing a Sequence Repeats in a Sequence Sequence Comparison by Hashing Sequence Comparison with at most l Mismatches Sequence Comparison by Statistical ContentDynamic Programming Alignment of Two Sequences The Number of Alignments Shortest and Longest Paths in a Network Global Distance Alignment Global Similarity Alignment Fitting One Sequence into Another Local Alignment and Clumps Linear Space Algorithms Tracebacks Inversions Map Alignment Parametric Sequence ComparisonsMultiple Sequence Alignment The Cystic Fibrosis Gene Dynamic Programming in r-Dimensions Weighted-Average Sequences Profile Analysis Alignment by Hidden Markov Models Consensus Word AnalysisProbability and Statistics for Sequence Alignment Global Alignment Local Alignment Extreme Value Distributions The Chein-Stein Method Poisson Approximation and Long Matches Sequence Alignment with ScoresProbability and Statistics for Sequence Patterns A Central Limit Theorem Nonoverlapping Pattern Counts Poisson Approximation Site DistributionsRNA Secondary Structure Combinatorics Minimum Free-energy Structures Consensus foldingTrees and Sequences Trees Distance Parsimony Maximum Likelihood TreesSources and Perspectives Molecular Biology Physical Maps and Clone Libraries Sequence Assembly Sequence Comparisons Probability and Statistics RNA Secondary Structure Trees and SequencesReferencesProblem Solutions and HintsMathematical NotationAlgorithm IndexAuthor IndexSubject Index
Keywords: Computational biology; Molecular biology--Mathematics; Molecular biology--Statistical methods; Molecular genetics--Mathematics; Molecular genetics--Statistical methods